A Systematic Literature Review on IoT-Enabled Flood Disaster Mitigation Systems: Technologies, Challenges, and Future Directions - Poudyal, Youba Raj; Sharma, Gajendra (Journal of Science and Technology, 2026)
Flood disasters are happening more often and are getting worse because of climate change and urbanization. This means that we need advanced mitigation systems that use the latest technologies. This systematic literature review analyzes IoT-enabled flood disaster mitigation systems, emphasizing their technological underpinnings, implementation obstacles, and prospective research trajectories. We examine the functions of IoT and AI in flood management, flood risk assessment methodologies, and mitigation strategies, while also investigating the social and economic consequences of floods and the application of remote sensing, UAVs, and social media in disaster communication. The review employs a systematic approach to identify, assess, and integrate pertinent studies, guaranteeing a thorough comprehension of the present research landscape. Our research shows that IoT-based systems greatly enhance the ability to monitor floods in real time and give early warnings. However, there are still challenges